Odpowiedź :
a) x³-5x²+2x-10+2x³+6x+7=3x³-5x²+8x-3
b)x³-5x²+2x-10-(2x³+6x+7)=x³-5x²+2x-10-2x³-6x-7=-x³-5x²-4x-17
b)x³-5x²+2x-10-(2x³+6x+7)=x³-5x²+2x-10-2x³-6x-7=-x³-5x²-4x-17
Dodawanie :
x³-5x²+2x-10 + 2x³+6x+7= 3x³-5x²+8x -3
Odejmowanie:
x³-5x² +2x-10 - (2x³+6x+7)= x³-5x² +2x-10-2x³-6x-7= -x³-5x²-4x-17
x³-5x²+2x-10 + 2x³+6x+7= 3x³-5x²+8x -3
Odejmowanie:
x³-5x² +2x-10 - (2x³+6x+7)= x³-5x² +2x-10-2x³-6x-7= -x³-5x²-4x-17
W(x)=X³-5x²+2x-10
F(x)=2x³+6x+7
W(x)+F(x)=X³-5x²+2x-10+2x³+6x+7=3x³-5x²+8x-3
W(x)-F(x)=x³-5x²+2x-10-(2x³+6x+7)=x³-5x²+2x-10-2x³-6x-7=-x³-5x²-4x-17
F(x)=2x³+6x+7
W(x)+F(x)=X³-5x²+2x-10+2x³+6x+7=3x³-5x²+8x-3
W(x)-F(x)=x³-5x²+2x-10-(2x³+6x+7)=x³-5x²+2x-10-2x³-6x-7=-x³-5x²-4x-17